Mosquito and global dengue cases in a warming world - Joseph J Y Sung; Tsin Wen Yeo; Jie Hu; Benjamin P Horton; Yim Hung Lam Steve (BMJ Global Health)
Dengue presents a significant global health challenge, affecting 50–100 symptomatic infections every year and placing immense strain on healthcare systems in tropical and subtropical regions. However, future projections of dengue infections in a warming world remain unclear. We used the support vector machine (SVM) and artificial neural network (ANN) models with Aedes mosquitoes and dengue records from 1960 to 2019 to comprehensively assess the effects of climate change and socioeconomic conditions on the distribution of mosquitoes and the global dengue incidence rate. The SVM and ANN models were applied to project the global future incidence rate and infections during 2021–2040, 2041–2060 and 2061–2080 under various climate change and socioeconomic conditions in a 5 km spatial resolution. We found a geographical distribution expansion of Aedes mosquitoes and dengue in future years, especially in higher latitudes such as North America and Europe. It was estimated that 77 (confidence interval: 40 to 198) million yearly global infections will occur during 2041–2060 under the Shared Socio-economic Pathway SSP2-4.5, a 57% increase of 49 (26−127) million compared with 2000–2019. The rise in annual infections is primarily attributed to the growing incidence rates driven by rising temperatures and the enhanced suitability of Aedes aegypti, and an expanding human population. Our high-resolution projection provides support to local control measures to minimise health impacts from dengue. Specifically, the Aedes mosquito control programmes such as eliminating the Ae. aegypti breeding sites are recommended in Africa and South Asia, where dengue is particularly severe in all climate change and socioeconomic conditions.